"Gestión de becas para estudiantes regulares de pregrado de la UTEQ mediante una aplicación Web - Cruz Garcia, Paula Pamela (2016)
It was designed a Web System, that allows to automate the processes performed in Management Scholarship for Undergraduate Regular Students of the Quevedo State Technical University,in the Student Welfare Unit in the Social Work Area. There is a need to optimize the time and the adequacy of student information through a socioeconomic form via online, which is subjected to an evaluation by a data analysis, where the in charge of must set the parameters, indicators and variables according to the need that exists, using the points valuation method for the distribution of values. It was made the selection of beneficiaries to the types of scholarships like Economics Limited, Academic Excellence, Disability and High Performance Sports applying an appropriate mathematical model for the selection. If there falsehood in the socioeconomic profile of students be proceed to cancel the scholarship, to qualify for a scholarship is required be a regular student which has at least 60% of the selected learning unit. Is taken into consideration the academic performance of students for all the types of selection. The system was developed in platforms Netbeans 8.0.2,Postgres 9.4. and The RAD methodology was applied in the development of the system.The interview and direct observation were the techniques used for data collection, the deductive method was also used. With the development of the website, agility the scholarship management process and facilitate keeping track data management, so that it complies with the main objective of the research .